Crescimento, produtividade e eficiência de uso de nitrogênio na cultura da chia - Nunes, Anderson Rodrigues (2019)
Demand for healthy food has grown in recent years, increasing demand for chia. It is known that sowing date and nitrogen fertilization influence the growth, consequently, biomass production and grain yield of agricultural species, which includes chia. Thus, the objective of this work was to evaluate the influence of two sowing dates and five N rates on the agronomic characteristics of chia. A field experiment was carried out with two sowing dates (November / 2017 and January / 2018) combined with five nitrogen doses (0, 30, 60, 90 and 120 kg ha -1 ) in coverage. The experimental design was of randomized blocks in a 5 x 2 factorial scheme with four replications. The plants of the two central lines were evaluated, excluding the two lines of the border. Evaluations took place at the time of flowering and harvest. The variables evaluated in the field during flowering were: dry mass of leaves, main stems, branches and spikes; leaf area of stems and branches, leaf area index of stems and branches. At the time of harvest, plant height, stem diameter, number of branches, number and length of ears, dry shoot mass and stem and branch grain yield were evaluated. The nitrogen content in leaves, stems, branches and grains was determined using the sulfur digestion methodology. The sowing dates and N doses studied showed that the sowing of November provided a larger increase in all the growth parameters, due to the elongation of the crop cycle that is affected by the photoperiod, and the nitrogen rates influenced the variables because it was a nutrient that in excess causes greater vegetative growth. The production of chia grains for the dates differed, with higher yields at the 104 kg ha -1 dose at November sowing. January production was close to November production in the last dose of N tested. N concentrations in the leaves, stem, branches and grains were higher at the late sowing date, and responded differently from each other as N rates increased. Nitrogen recovery efficiency was decreasing at the doses applied in both sowing, being most noticed in the recommended sowing. The maximum technical and economic efficiency demonstrated close values, however, for greater economic viability, the dose of 104 kg ha -1 is more recommended. Both sowing dates and N rates influenced chia growth and productivity, and it is recommended to plant sowing in the month of November with the application of N at the dose of 104 kg ha -1 .